Quality culture & school climate development - Hartinah (Enrichment : Journal of Management, 2022)
This Study uses a qualitative descriptive method and type study. This is library research, with the destination will display how development culture quality school is critical and influential in forming a professionality human character-based education culture. Because School no just a receptacle or the place ongoing learning process activities teach however, how about the educators/resources available power capable create a conducive culture and climate so that serenity and a sense of security could feel in the environment, as well as necessary indicators noticed in develop culture quality and conducive climate school because the Education Law says every citizen have right same for getting a quality education, but in reality culture quality at School still found constraints with several influencing factors both internally and external like role leader yet maximum, communication, curriculum, teacher quality, facilities, learning process anyway committee school here several parts Becomes Duty paramount for stakeholders in the world of education until the moment this. Claims quality/quality education increase with progress knowledge and technology, global competition is increasingly strict and conscientious Public so that when managers education no capable solve internal problems School, so quality no capable follow compete globally as demands that. Temporary Culture quality is absent from role leaders, teachers, committees, and all school human resources. The sued gives a fulfilling exterior to all hope users (parents, students, and society), where education covers the quality of input, process, output, and outcome.